Analysis of Willingness To Pay Cassava Chips in Langkat Regency and Factors Affecting It - Siregar, Futri Medwina; Sihombing, Vista Uli (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Cassava chips are one of the popular processed cassava products with significant development potential. Langkat Regency, located in North Sumatra Province, is one of the regions with the largest agricultural potential in Indonesia, particularly in cassava production. In addition, the micro, small, and medium enterprise (MSMEs) sector in this region is also growing, especially in processing agricultural products into consumable foods such as cassava chips. This study has two main objectives: to estimate the willingness to pay (WTP) for cassava chips in Langkat Regenc and to analyze the factors that influence the level of WTP for cassava chips in the region. The analysis of willingness to pay for cassava chips uses the Contingent Valution Method (CVM), and the relationship between factors influencing the WTP value is analyzed using multiple linear regression. The average WTP of respondents for cassava chips is IDR 37,920 per kilogram. This average value is higher than market price of cassava chips in Langkat Regency, which is IDR 35,000 per kilogram. The variables of gender, income, and product image have a significant influence on the willingness to pay for cassava chips.